2022
DOI: 10.1200/jco.21.01308
|View full text |Cite|
|
Sign up to set email alerts
|

Five-Year Survival Outcomes From the PACIFIC Trial: Durvalumab After Chemoradiotherapy in Stage III Non–Small-Cell Lung Cancer

Abstract: PURPOSE The phase III PACIFIC trial compared durvalumab with placebo in patients with unresectable, stage III non–small-cell lung cancer and no disease progression after concurrent chemoradiotherapy. Consolidation durvalumab was associated with significant improvements in the primary end points of overall survival (OS; stratified hazard ratio [HR], 0.68; 95% CI, 0.53 to 0.87; P = .00251) and progression-free survival (PFS [blinded independent central review; RECIST v1.1]; stratified HR, 0.52; 95% CI, 0.42 to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
455
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 707 publications
(488 citation statements)
references
References 25 publications
26
455
1
6
Order By: Relevance
“…The results of this single institution retrospective analysis demonstrate that for patients with locally advanced stage III NSCLC, the use of adjuvant durvalumab after completion of chemoradiation improves PFS and OS compared to historic controls treated with chemoradiation alone. Although most patients in our trial did not conform to eligibility criteria for inclusion in the PACIFIC trial because of delay in starting adjuvant durvalumab ( n = 51), history of immune disease ( n = 3), or ECOG status ≥2 ( n = 4), the improved PFS and OS with adjuvant durvalumab observed in our study are consistent with outcomes reported in the PACIFIC trial and other real‐world studies 7–18 . The real‐world data presented in this study, although limited, suggest that future clinical trials consider inclusion of patients who begin durvalumab therapy beyond 42 days after completion of chemoradiation, have a prior history of immune disease, or have an ECOG performance status ≥2.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this single institution retrospective analysis demonstrate that for patients with locally advanced stage III NSCLC, the use of adjuvant durvalumab after completion of chemoradiation improves PFS and OS compared to historic controls treated with chemoradiation alone. Although most patients in our trial did not conform to eligibility criteria for inclusion in the PACIFIC trial because of delay in starting adjuvant durvalumab ( n = 51), history of immune disease ( n = 3), or ECOG status ≥2 ( n = 4), the improved PFS and OS with adjuvant durvalumab observed in our study are consistent with outcomes reported in the PACIFIC trial and other real‐world studies 7–18 . The real‐world data presented in this study, although limited, suggest that future clinical trials consider inclusion of patients who begin durvalumab therapy beyond 42 days after completion of chemoradiation, have a prior history of immune disease, or have an ECOG performance status ≥2.…”
Section: Discussionsupporting
confidence: 82%
“…The use of immunotherapy in patients with stage IV NSCLC is associated with improved overall survival (OS) and progression free survival (PFS) 6 . The PACIFIC trial reported improved outcomes in carefully selected patients with unresectable stage III NSCLC treated with 1 year of adjuvant durvalumab following chemoradiation compared to a control group treated with chemoradiation followed by placebo 7–11 . Subsequent reports from real‐world single and multicenter studies confirmed the improved OS and PFS reported in the PACIFIC trial 12–18 .…”
Section: Introductionmentioning
confidence: 95%
“…After more than three decades of limited progress in treating extensive-stage small-cell lung cancer (ES-SCLC), the introduction of immune checkpoint inhibitors, particularly the programmed death ligand-1 (PD-L1) inhibitors durvalumab and atezolizumab, has provided significant improvements in overall survival (OS). 1 , 2 Immune checkpoint inhibitors have shown impressive durable survival benefit in non-small-cell lung cancer; 3 , 4 , 5 however, as immunotherapy trials in ES-SCLC are comparatively recent, the extent to which long-term survival can be improved in this setting is not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…4-6 Furthermore, recent 5-year data from PACIFIC demonstrated robust and sustained OS benefit plus durable PFS with durvalumab, with 5-year OS and PFS rates of 42.9% and 33.1%, respectively. 7…”
Section: Introductionmentioning
confidence: 99%
“…AFFILIATIONS 1 Yale Cancer Center, New Haven, CT 2 Hospital de la Santa Creu i Sant Pau, Barcelona, Spain 3 Gustave Roussy, Villejuif, France 4 Institut Catal à d'Oncologia, Badalona-Hospital Germans Trias i Pujol, Barcelona, Spain 5 Cross Cancer Institute, Edmonton, AB, Canada 6 Centre Hospitalier Intercommunal de Cr éteil, Cr éteil, France 7 Consorcio Hospitalario Provincial de Castell ón, Castell ón, Spain 8 Cancer Center of Kansas, Wichita, KS 9 University of Colorado Anschutz Medical Campus, Aurora, CO 10 AstraZeneca, Cambridge, United Kingdom 11 AstraZeneca, Gaithersburg, MD 12 Abramson Cancer Center, University of Pennsylvania, Philadelphia, PA 13…”
mentioning
confidence: 99%